7. Resurvey of Strain Grids at Mizuho Camp and Y 200(II. GLACIOLOGICAL OBSERVATION IN MIZUHO PLATEAU-WEST ENDERBY LAND AREA, EAST ANTARCTICA, 1974-1975) - SATOW, Kazuhide (National Institute of Polar Research, 1977)
P(論文) departmental bulletin paper